An Arduino-Based RFID Platform for Animal Research - Bridge, Eli S.; Wilhelm, Jay; Pandit, Meelyn M.; Moreno, Alexander; Curry, Claire M.; Pearson, Tyler D.; Proppe, Darren S.; Holwerda, Charles; Eadie, John M.; Stair, Tez F.; Olson, Ami C.; Lyon, Bruce E.; et al. (Frontiers in Ecology and Evolution, 2019)
Radio Frequency Identification (RFID) technology has been broadly applied in the biological sciences to yield new insights into behavior, cognition, population biology, and distributions. RFID systems entail wireless communication between small tags that, when stimulated by an appropriate radio frequency transmission, emit a weak, short-range wireless signal that conveys a unique ID number. These tags, which often operate without a battery, can be attached to animals such that their presence at a particular location can be detected by an RFID reader. This paper describes an RFID data-logging system that can serve as the core for a wide variety of field and laboratory applications for monitoring the activities of individual animals. The core electronics are modeled on an Arduino circuit board, which is a hobbyist electronics system. Users can customize the hardware and software to accommodate their needs. We demonstrate the utility of the system with cursory descriptions of three real-world research applications. The first is a large-scale deployment that was used to examine individual breeding behaviors across four local populations of Wood Ducks. The second application employed an array of RFID-enabled bird feeders that allowed for tests of spatial cognition. Third, we describe a nest-box monitoring system that both records visits from breeding birds and administers experimental treatments, such as increasing temperature or playing audio recordings, in accordance to the presence/absence of individual birds. With these examples we do not attempt to relate details with regard to research findings; rather our intent is to demonstrate some of the possibilities enabled by our low-cost RFID system. Detailed descriptions, design files, and code are made available by means of the Open Science Framework.